Ammoniacal nitrogen reclamation by membrane distillation from high ammonia polluted solutions - Zoungrana, Ali; Zengin, Ismail Hakki; Turk, Oruc Kaan; Cakmakci, Mehmet (SPRINGER INT PUBL AG, 2020)
Landfill leachate is high-strength wastewater containing harmful pollutants and very rich in ammonia (NH3), an undesired element in wastewaters. NH3 is used as a liquid fertilizer in agriculture and as a reactant in many other fields. The present study investigated the reclamation of NH3 during the treatment of middle-age landfill leachate by direct contact membrane distillation (DCMD) with polytetrafluoroethylene (PTFE) and polyvinylidene difluoride (PVDF) 0.45 mu m pore size membranes. Synthetic and real wastewaters were used during the study. pH, temperature and salt content of the solution highly affected the reclamation efficiency of NH3. Low reclamation of NH3 from the real leachate was reported compared to synthetic solutions, due to the solution characteristic. With low salinity, high salinity synthetic solution and real landfill leachate as feed solutions heated to 60 degrees C, the reclamation efficiency of NH3 by PTFE membrane, determined as the best membrane in this study, was 81.1%, 97.6% and 58.4, respectively. The autopsy of the PTFE membrane by SEM analysis, FTIR and contact angle, after 72 h operation showed very little damage to the membrane but depicted the deposition of some particles on the membrane surface, causing the flux to drop from 12.7 to 11.9 L/m(2) h.
Keywords: Ammonia reclamation; Hydrophobic membrane; Landfill leachate; Membrane distillation; LANDFILL LEACHATE TREATMENT; WASTE-WATER; REMOVAL; OSMOSIS; SEPARATION; SYSTEM; FENTON; SBR; Chemistry